Application of blue light-emitting diode in combination with antimicrobials or photosensitizers to inactivate Escherichia coli O157:H7 on fresh-cut apples and cherry tomatoes. (January 2022) - Hyun, Jeong-Eun; Moon, Sung-Kwon; Lee, Sun-Young
Abstract: The aim of this study was to investigate the antibacterial effect of blue light-emitting diode (blue-LED; 460–470 nm) combined with various chemicals at inactivating Escherichia coli O157:H7 on the surface of agar media and fresh produce. Fresh-cut apples and cherry tomatoes were immersed in antimicrobials (1 % ascorbic acid, 0.025 % carvacrol, and 0.125 % citric acid) or photosensitizers (0.0078 % curcumin and 0.0078 % riboflavin) on the inactivation of E. coli O157:H7 during illumination for 5 d at 4 °C. When carvacrol was combined with blue-LED, there was a higher reduction in E. coli O157:H7 populations compared with treatment with blue-LED, an antimicrobial, or a photosensitizer alone. In particular, among the chemicals tested, the populations of E. coli O157:H7 on cherry tomatoes was reduced below detectable level (<1.48 log10 CFU/g) when treated with the combination of carvacrol or ascorbic acid and blue LED after storage of 5 d, without causing color deterioration. BI values were significantly reduced by the combined treatment of carvacrol (38.30), citric acid (37.67) or ascorbic acid (39.85) with blue LED for 5 d when compared to control (59.36). These results indicates that blue-LED in combination with antimicrobials or photosensitizers, may be applied to extend the shelf-life of fresh-cut fruits and vegetables during distribution without causing color deterioration. Highlights: Blue-LED increases the effectiveness of antimicrobials or photosensitizers. Antimicrobial in combination with LED could inhibit the growth of E. coli O157:H7. Carvacrol in combination with LED could be used to inhibit pathogens on fresh produce. Combination treatment strategies may improve food safety and shelf-life.